2016
DOI: 10.1038/srep32350
|View full text |Cite
|
Sign up to set email alerts
|

SOX9-regulated cell plasticity in colorectal metastasis is attenuated by rapamycin

Abstract: The cancer stem cell (CSC) hypothesis proposes a hierarchical organization of tumors, in which stem-like cells sustain tumors and drive metastasis. The molecular mechanisms underlying the acquisition of CSCs and metastatic traits are not well understood. SOX9 is a transcription factor linked to stem cell maintenance and commonly overexpressed in solid cancers including colorectal cancer. In this study, we show that SOX9 levels are higher in metastatic (SW620) than in primary colorectal cancer cells (SW480) der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…In this work, we found that modulation of SOX9 levels affects BMI1 expression in multiple cancer cell lines in vitro and in vivo. These results are in agreement with previous studies that linked SOX9 and BMI1 in primary fibroblasts and colorectal CSCs 23,33 . This regulation is likely to be direct since chromatin immunoprecipitation experiments have shown that SOX9 binds to the promoter of BMI1 in different types of cells and contexts 33,41 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this work, we found that modulation of SOX9 levels affects BMI1 expression in multiple cancer cell lines in vitro and in vivo. These results are in agreement with previous studies that linked SOX9 and BMI1 in primary fibroblasts and colorectal CSCs 23,33 . This regulation is likely to be direct since chromatin immunoprecipitation experiments have shown that SOX9 binds to the promoter of BMI1 in different types of cells and contexts 33,41 .…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, our results show that there is also a positive correlation between SOX9 and BMI1 expression, and negative between SOX9 and p21 CIP in clinical samples. In line with this, previous studies analyzed the correlation between SOX9, BMI1 and p21 CIP in different types of cancers and showed independently that SOX9 regulates proliferation through a positive correlation with BMI1 and an inverse correlation with p21 CIP expression 23,31,[33][34][35] . Together, these results highlight that BMI1 is a relevant mediator of SOX9 in promoting tumor malignancy and show the importance of this axis in cancer progression, thus providing new therapeutic possibilities, such as BMI1 inhibition, a strategy that is being currently evaluated in different cancer clinical trials.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…20 In colon cancer, SOX9 was overexpressed and high expression of SOX9 promoted migration, invasion and epithelial mesenchymal transition of colon cancer cell lines. 22 In our study, we found that LEF1-AS1 promoted migration, invasion and anchorage-independent growth of colon cancer cells in vitro and facilitated tumor xenograft growth and lung metastasis in vivo. In addition, LEF1-AS1 mediated SOX9 expression by serving as a molecular sponge for miR-30-5p, and SOX9 restoration abolished the effects caused by LEF1-AS1 knockdown in colon cancer cells.…”
Section: Introductionsupporting
confidence: 50%
“…Compared with the prominent expression of Ki-67 in the cryptic parts, in the normal-appearing parts, adenoma displayed a relatively even level of expression of the protein throughout the epithelial tumor tissue. Moreover, expression of Sox-9 as a self-renewal and proliferation marker of colorectal cancer (34) was also downregulated in the tumor mass by the recombinant probiotic bacteria ( Figure 12C). Despite extensive activation of an EGFR-linked signal, cell growth-related fingerprints in the tumor mass faded with EGF-EcN colonization.…”
Section: Figure 8 Effects Of Egf-ecn On Nsaid-induced Ulcerative Injmentioning
confidence: 96%